Choreographing Cape Town through Goema music and dance - Inglese, Francesca (International Library of African Music, 2014)
In this article, I address the distinctive spatial practices of Minstrel Carnival participants, exploring the ways in which paraders use their bodies to collectively lay claim to Cape Town and access urban space through sonic and embodied performances. Recent scholarship has called attention to the central narratives of slavery and emancipation contained within the Minstrel Carnival, as well as the symbolic significance of the Carnival's re-appropriation of city space in relation to the coloured community's colonial and apartheid experiences of dispossession, forced removals, and social dislocation.
Keywords: African Music